RELATIONSHIP BETWEEN SELF CONFIDENCE AND INTERPERSONAL RELATIONSHIP AMONG HIGHER SECONDARY STUDENTS AND VOCATIONAL HIGHER SECONDARY STUDENTS - K. P. Suresh, Jismy Raj and Liji Joseph (PEDAGOGICS: A Journal from School of Pedagogical Sciences, 2017)
The present study was intended to measure the relationship between self confidence and interpersonal relationship of higher secondary school students. The data was collected from higher secondary and vocational higher secondary school students by administrating the self confidence and interpersonal relationship scale. The study proved that there is significant relationship between self confidence and interpersonal relationship among Higher Secondary School and Vocational Higher Secondary School students.